(untitled) (INNOVATIVE ECONOMY, 2019)
Vodovozov Ye.N., Palant O.Yu. CRITERIA FOR OPTIMIZATION OF URBAN TRANSPORT CONNECTION IN KYIV Purpose. The aim of the article is the provision of scientifically substantiated practical recommendations for the optimization of the public transport network in Kyiv. Methodology of research. The research is based on a strictly scientific approach and conducted using the methods of analysis, comparison and synthesis (to study the domestic and foreign experience of existing theoretical and methodological provisions on route network optimization), classification and ranking (when developing a complex of innovative approaches to the studied object) as well as mathematical statistics (for the processing and analysis of input data) and economic-mathematical modelling (to investigate the relationships between factors that affect development urban public transport and quality assessment of enterprises) with careful evaluation of the obtained results. A strategy for collecting information on urban passenger transport has also been developed. Findings. The analysis of the conducted researches proves that gradually optimized by the offered way the route network of Kiev serves all four selected optimization criteria. It is established that the network reflects the demand for travel, meets the needs of passengers, providing a wide range of choices of routes of several options, and at least one of them will be minimally different from the shortest between the points of departure and destination. It is proved that the network serves the needs of the city by unloading the busy traffic situation of the capital. It is substantiated that increasing the economic efficiency of the operation of transport enterprises by reducing the operating costs of maintaining the network and increasing the flow of passengers will give more income for enterprises-carriers and reduce their dependence on local budgets. In addition, it is determined that the social well-being of citizens will be enhanced through the provision of quality transport utilities. It is shown how environmental protection will be provided by replacing part of the bus routes with trolley buses and using larger vehicles instead of several smaller units. Originality. For the first time, it is proposed to divide Kiev into 12 conditional transport areas and to apply the optimization process gradually for each of them, which subsequently allowed using the computer to check the proposed updated itinerary for viability within the transport model of the whole city. The sequence of the found algorithm was repeatedly repeated in order to feel the combined effect of the proposals. Practical value. The results of the study can be used by the Kyiv City State Administration to optimize the city’s route network. Key words: public transport, route network optimization, passenger traffic, transport model, rolling stock.